Touch the wounds: on suffering, trust, and transformation - Halík, Tomáš (University of Notre Dame Press, 2025)
"One of the most important voices in contemporary Catholicism, Tomáš Halík argues that Christians can discover the clearest vision of God not by turning away from suffering but by confronting it. Halík calls upon us to follow the apostle Thomas's example: to see the pain, suffering, and poverty of our world and to touch those wounds with faith and action. It is those expressions of love and service, Halík reveals, that restore our hope and the courage to live, allowing true holiness to manifest itself. Only face-to-face with a wounded Christ can we lay down our armor and masks, revealing our own wounds and allowing healing to begin. Weaving together deep theological and philosophical reflections with surprising, trenchant, and even humorous commentary on the times in which we live, Halík offers a new prescription for those lost in moments of doubt, abandonment, or suffering. Rather than demanding impossible, flawless faith, we can look through our doubt to see, touch, and confront the wounds in the hearts of our neighbors and--through that wounded humanity, which the Son of God took upon himself--see God"--Book jacket flap